Ultrasound Assessment of Amniotic Fluid in Predicting Adverse Outcome in Prolonged Pregnancy (Medicine Today, 2013)
DoIDOI: http://dx.doi.org/10.3329/medtoday.v24i2.15006 Medicine Today 2012 Vol.24(2): 55-58